Angioid Streaks in Types I and II Congenital Dyserythropoietic Anaemia (CDA) - Frimmel, S.; Kniestedt, C. (Klinische Monatsblätter für Augenheilkunde, 2016)
Background. Angioid streaks (AS) are visible irregular breaks in Bruchʼs membrane, extending radially from the optic nerve head and with overlaying atrophic retinal pigment epithelium. In 50 % of patients, AS are associated with Pseudoxanthoma elasticum, Ehlers-Danlos syndrome, sickle cell anaemia or Pagetʼs disease. In 50 % of patients, AS are idiopathic. Congenital Dyserythropoietic Anaemia (CDA) is a rare, inherited disorder of ineffective erythropoiesis with morphologically abnormal erythroblasts. CDA was first recognised as a separate entity in 1968 and classified into three main groups. CDA demographics have identified 614 known families and > 700 cases worldwide. A few case reports of AS in CDA I and III have been published, but there is no report of AS in CDA II, the most frequent of the CDAs, as well no follow-up. History and Signs. 8 eyes of 4 CDA patients were examined. The CDA I patients were a 46 year old man and a 52 year old woman. They were first seen in 2009 and followed up for 9 and 11 months, respectively. The 2 female CDA II patients were seen in 2010 and were aged 35 and 42 years at first presentation. Vision, Amsler grid, optical coherence tomography (OCT), fundus pictures and fluorescent angiography were performed. Blood was drawn for neutrophil elastase determination (ELA2). Therapy and Outcome. All patients showed bilateral AS. Mean best corrected visual acuity was 20/20 without metamorphopsia and with normal OCT. During the follow-up period, no progression occurred. No choroidal neovascularisation (CNV) was detected. ELA2 serum levels were normal. Conclusions. This is the first report of AS in CDA II and the first follow-up in CDA I. No evidence of progression was seen within this period of time. Longer follow-up is needed to detect whether AS progresses. All patients with AS should be seen by an ophthalmologist on a regular basis. The risk of CNV is given. Therapy is possible and the outcome is best if the CNV is recognised and treated early.
Keywords: angioid streaks; congenital dyserythropoietic anaemia type I and II; choroidal neovascularisation